ANALISIS PENGARUH KARAKTERISTIK INDIVIDU DAN PEMBERDAYAAN TERHADAP KOMITMEN ORGANISASIONAL DIMEDIASI KEPUASAN KERJA (STUDI PADA SEKOLAH TINGGI AGAMA ISLAM WALI SEMBILAN SEMARANG (SETIA WS) - Ni’am, Kamalun (Students Journal of Economic and Management, 2012)
The study ecxamines the impact between individual characteristics and empowerment toward organizational commitment with job satisfaction as a mediated variables at Sekolah Tinggi Agama Islam Wali Sembilan Semarang (Setia WS). The purpose of this study is to find empirical evidence about the presence / the absence of a). the positive effect of individual characteristics and job satisfaction, b). the positive effect of empowerment and job satisfaction, c). the positive effect of individual characteristics and organizational commitment, d). the positive effect of empowerment and organizational commitment, and e). the positive effect of job satisfaction and organizational commitment. The respondent of this study all of employees who worked at Sekolah Tinggi Agama Islam Wali Sembilan Semarang (Setia WS), which amount 108 employees and the research used cencus technique method. Sample of this research is amount 96 employees. To analyse the research instrument used validity test with factor analysis, and reliability test with alpha cronbach, and multiple linier regression, and t statistics to prove the research hypothesis and mediated effect to test job satisfaction as mediated. The result show that individual characteristics and empowerment have positive and significance influence to job satisfaction, individual characteristics, empowerment and job satisfaction have positive and significance influence to organizational commitment. The result of this research is indicated that the impact of individual characteristics and empowerment toward organizational commitment mediated by job satisfaction Keywords :Â Â individual characteristics, empowerment, job satisfactionÂ and organizational commitment.